Limbah Batu Lahar Gunung Agung Sebagai Bahan Campuran Beton Dalam Upaya Kelestarian Lingkungan - I Made Sastra Wibawa; Shinta Enggar Maharani (Jurnal Ecocentrism, 2023)
There is a lot of excavation of materials for concrete mixtures in nature so that their existence is dwindling. Efforts are needed to find substitute materials but still maintain the quality of the concrete obtained. The purpose of this study is to determine the percentage of waste lava stone as a substitute for coarse aggregate in order to obtain compressive strength according to the plan and to determine the effect of environmental sustainability after waste stone is used as a concrete mixture. This study was conducted at the Laboratory of the Faculty of Engineering Unmas Denpasar by making a cylindrical specimen with a diameter of 15 cm and a height of 30 cm. Replacement of lava rock waste was made in 5 categories P0, P1, P2, P3, P4 with 8 specimens in each category, where the compressive strength test was carried out at the age of 28 days, with category P0 as a control without adding lava rock waste. The results showed that there was an increase in the compressive strength of concrete in categories P1 and P2, P3 and a decrease in the compressive strength of concrete in category P4, but the decrease that occurred design compressive strength.